The Use of Code Switching by the English Teacher in Teaching-Learning Activities - Nashruddin, Nashruddin; Aisyah, Sitti; Syam, Ummi Khaerati (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2024)
The present research aimed at finding out: (1) the forms of code switching used by English teacher in teaching-learning activities; and (2) the reasons of the English teacher for using the code switching in teaching-learning activities. This study employs qualitative research design. The research subject is an English teacher for the 8th grade students at SMP Dirgantara Makassar. The research data were collected by using observation and interview. The data obtained were analyzed by using the procedure proposed by Creswell (2013), consisting of data managing, data organizing, giving a memo, describing, classifying, and data interpretation. From the results of data analysis, it was found that (1) the English teacher used 3 form of code switching in teaching-learning activities: inter-sentential switching, intra-sentential switching, and tag switching. (2) The teacher applied the code switching in teaching-learning activities for 5 reasons: for confirming, for motivating, for introducing unfamiliar vocabularies, for explaining the grammar, and for translating. Generlly, the use of code switching by English teacher in teaching-learning activities has positive implication for students in teaching English as a foreign language.